Impacto da divulgação da pesquisa sobre biocurativos e avaliação psicosocial dos pacientes - Cotrim, Ondina Silvia [UNESP]; Silva, Lisiane Lange da; Deffune, Elenice [UNESP] (My University, 2013)
The objective of this article was to analyze the impact of the dissemination of results from scientific research regarding the use of bio bandages for the treatment of patients with chronic wounds which present a difficult therapeutic approach. There was an increase in demand for bio bandages, via e-mail or telephone, after two reports were nationally broadcasted by two television stations. For a period of 10 years, the average of patients who looked for help did not exceed the number of 250 patients a year. However, in the first 10 days subsequent to the reports, 548 e-mails from patients were received. Not to mention the number of requests by phone, which was three times higher than those made by e-mail during the same period. From this fact, it can be inferred the importance of the re-evaluation of the treatment of patients with chronic wounds in the country, with a more systemic view on public health. Patients selected for the clinical protocol had multidisciplinary follow-up and responded to a structured questionnaire from the perspective of a qualitative research. The patients' average profile belongs to B1 social class. Female white patients, with an average age of 63, have had open lesions for a period that vary from six months to 30 years. Male patients practice more sports activities, while female patients are more involved in religious activities and craft work. Most patients have a technological profile; they believe in medicine innovations and are confident in the treatment. It is also the opinion of an expressive majority that the chronic wounds (CW) caused not only a great impact on them, but also in their relatives’ lives. This fact draws attention to the need of having a more comprehensive care in relation to non- chronification.

O objetivo deste artigo foi analisar o impacto da divulgação de resultados científicos referentes ao uso de biocurativos para tratamento de pacientes com feridas crônicas e que apresentam uma difícil abordagem terapêutica. A procura pelo biocurativo via e-mail ou telefone, sofreu um aumento demanda após a veiculação de reportagens em duas emissoras de televisão de abrangência nacional. Por um período de 10 anos, a média de pacientes que buscaram auxílio não excedeu o número de 250 pacientes ao ano. Entretanto, nos primeiros 10 dias subsequentes à veiculação das reportagens, foram recebidos 548 e-mails de pacientes. Isso sem mencionar o número de pedidos por telefone, que foi três vezes maior do que aqueles feitos por e-mail, no mesmo período. Esse fato permite destacar a importância da reavaliação do tratamento de pacientes com feridas crônicas no país, com uma visão mais sistêmica de saúde pública. Pacientes selecionados para o protocolo clínico tiveram acompanhamento multidisciplinar e responderam a um questionário semiestruturado sob a ótica de uma pesquisa qualitativa. O perfil médio dos pacientes pertence à classe social B1. Pacientes do gênero feminino, cor branca e com idade média de 63 anos, tem apresentado lesões abertas por um período que pode variar de seis meses a 30 anos. Os pacientes do gênero masculino praticam mais atividades esportivas, ao passo que pacientes do sexo feminino ocupam-se mais das atividades religiosas e de trabalhos manuais. A maioria dos pacientes tem um perfil tecnológico; acreditam nas inovações da medicina e estão confiantes no tratamento. É também a opinião de uma expressiva maioria que as feridas crônicas (FC) causaram não somente um grande impacto em suas vidas, mas também de seus familiares. Esse fato é o que chama a atenção a respeito da necessidade de haver um atendimento mais global em relação à não cronificação.
Impact of research dissemination on bio bandages and psychosocial assessment of patients
Keywords: Chronics wounds; Biological dressing; Life quality; Feridas crônicas; Biocurativo; Qualidade de vida